Designing and testing a blockchain application for patient identity management in healthcare. Issue 3 (9th February 2021) - Khurshid, Anjum; Holan, Cole; Cowley, Cody; Alexander, Jeremiah; Harrell, Daniel Toshio; Usman, Muhammad; Desai, Ishav; Bautista, John Robert; Meyer, Eric
Abstract: Objective: Healthcare systems suffer from a lack of interoperability that creates "data silos, " causing patient linkage and data sharing problems. Blockchain technology's unique architecture provides individuals greater control over their information and may help address some of the problems related to health data. A multidisciplinary team designed and tested a blockchain application, MediLinker, as a patient-centric identity management system. Methods: The study used simulated data of "avatars" representing different types of patients. Thirty study participants were enrolled to visit simulated clinics, and perform various activities using MediLinker. Evaluation was based on Bouras' criteria for patient-centric identity management and on the number of errors in entry and sharing of data by participants. Results: Twenty-nine of the 30 participants completed all study activities. MediLinker fulfilled all of Bouras' criteria except for one which was not testable. A majority of data errors were due to user error, such as wrong formatting and misspellings. Generally, the number of errors decreased with time. Due to COVID-19, sprint 2 was completed using "virtual" clinic visits. The number of user errors were less in virtual visits than in personal visits. Discussion: The evaluation of MediLinker provides some evidence of the potential of a patient-centric identity management system using blockchain technology. The results showed a working system where patients have greater control over their information and can also easily provide consent for use of their data. Conclusion: Blockchain applications for identity management hold great promise for use in healthcare but further research is needed before real-world adoption.